ANALISIS KUALITAS PELAYANAN PUBLIK PADA DINAS PENCEGAHAN DAN PENANGGULANGAN KEBAKARAN KOTA BANDUNG - Mira Veranita; Dedeng Yusuf Maolani (Centre for Asian Social Science Research (CASSR), FISIP, UIN Bandung, 2018)
This study aims to find out how the quality of service at the Bandung Fire Prevention and Control Agency. This study uses qualitative research methods with data collection techniques in the form of observation, interviews, and documentation studies. While the data processing and analysis techniques use triangulation. The results showed that the quality of service at the Bandung City Fire Prevention and Control Agency was measured through 4 (four) aspects, namely aspects of convenience, aspects of speed, aspects of accuracy, and security aspects tend not to run optimally. This can be seen from the large number of objects that cannot be saved during a fire event. Such as residential buildings, public buildings, kiosks, shoping centers and so on.